PENGARUH TEMAN SEBAYA, POLA ASUH DAN PENGGUNAAN MEDIA SOSIAL DENGAN PERILAKU SEKS PRANIKAH PADA REMAJA DI SMK X KOTA DEPOK - Tiara, Intan; Kasumawati, Frida; Listiana, Ida; Amala, Lulu (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2025)
ABSTRACTAdolescence is a stage of growth after puberty to adulthood, and also a transition period from childhood to adulthood. According to the WHO, adolescence is grouped at the age of 10-19 years; the adolescent group is a large population of the world. The method in this study uses an analytical observational method with a cross-sectional design. The results of this study indicate that there is a relationship between peers and adolescent sexual behavior with a p value = 0.033 (p = α 0.05), there is no significant relationship between family roles and adolescent sexual behavior with a value of (P Value 0.21) α (0.05) and a significant relationship between social media and adolescent sexual behavior with a value of (P Value 0.21) α (0.05). Premarital sexual behavior is a behavior that can have long-term negative impacts on adolescents, including psychological impacts, social impacts, and physical impacts. Therefore, special attention is needed for adolescents, because if unhealthy sexual urges arise, it will lead to irresponsible sexual behavior and can damage the future of adolescents. Many factors influence premarital sexual behavior, including peers and sources of information. Suggestion: This activity can provide further understanding and awareness of adolescents regarding the impact of risky sexual behavior. This activity is carried out in an effort to provide knowledge to adolescents so that they have a positive self-concept in the form of religion and morals. ABSTRAKMenurut WHO (2020), internal stigma adalah orang diberi label, Remaja merupakan suatu tahapan pertumbuhan sesudah pubertas sampai dewasa, dan juga masa transisi dari anak-anak ke dewasa. Menurut WHO masa remaja dikelompokkan pada usia 10-19 tahun, kelompok remaja merupakan populasi yang besar dari penduduk dunia. Metode dalam penelitian ini menggunakan metode observasional analitik dengan rancangan cross sectional. Hasil dalam penelitian ini menunjukan bahwa ada hubungan teman sebaya dengan perilaku seksual remaja dengan nilai p value = 0,033 (p=α 0,05), tidak ada hubungan bermakna antara peran keluarga dengan perilaku seksual remaja dengan diperoleh nilai (P Value 0,21) α (0.05) dan hubungan bermakna antara media sosial dengan perilaku seksual remaja dengan diperoleh nilai (P Value 0,21) α (0.05). Perilaku seks pranikah merupakan perilaku yang dapat menimbulkan dampak negatif yang bersifat jangka panjang pada remaja diantaranya dampak psikologis, dampak social dan dampak fisik. Maka dari itu diperlukan perhatian khusus pada remaja, karena bila timbul dorongan-dorongan seksual yang tidak sehat akan menimbulkan perilaku seksual yang tidak bertanggung jawab dan dapat merusak masa depan remaja. Banyak faktor yang mempengaruhi perilaku seks pranikah diantaranya teman sebaya dan sumber informasi. Saran: melalui kegiatan ini dapat memberikan pemahaman lebih jauh dan kesadaran remaja mengenai dampak perilaku seksual yang beresiko. Kegiatan ini dilakukan dalam upaya memberikan pengetahuan pada remaja agar memiliki konsep diri berupa agama dan moral yang positif. ABSTRACTAdolescence is a stage of growth after puberty to adulthood, and also a transition period from childhood to adulthood. According to WHO, adolescence is grouped at the age of 10-19 years, the adolescent group is a large population of the world's population. The method in this study uses an analytical observational method with a cross-sectional design. The results of this study indicate that there is a relationship between peers and adolescent sexual behavior with a p value = 0.033 (p = α 0.05), there is no significant relationship between family roles and adolescent sexual behavior with a value of (P Value 0.21) α (0.05) and a significant relationship between social media and adolescent sexual behavior with a value of (P Value 0.21) α (0.05). Premarital sexual behavior is a behavior that can have long-term negative impacts on adolescents including psychological impacts, social impacts and physical impacts. Therefore, special attention is needed for adolescents, because if unhealthy sexual urges arise, it will lead to irresponsible sexual behavior and can damage the future of adolescents. Many factors influence premarital sexual behavior, including peers and sources of information. Suggestion: through this activity, it can provide further understanding and awareness of adolescents regarding the impact of risky sexual behavior. This activity is carried out in an effort to provide knowledge to adolescents so that they have a positive self-concept in the form of religion and morals